Factors associated with patients with gestational diabetes in Japan being at increased risk of requiring intensive care. Issue 2 (14th November 2017) - Yamashita, Hiroshi; Yasuhi, Ichiro; Kugishima, Yukari; Sugimi, So; Umezaki, Yasushi; Suga, Sachie; Fukuda, Masashi; Kusuda, Nobuko
Abstract: Objective: To investigate factors associated with high‐risk gestational diabetes (GDM) among patients with GDM. Methods: The present retrospective study included women with singleton pregnancies diagnosed with GDM using International Association of Diabetes and Pregnancy Study Group criteria at a single tertiary perinatal care center in Japan between July 1, 2010, and October 31, 2014. High‐risk GDM was defined as patients who required at least 20 units of insulin therapy a day, delivering a large‐for‐gestational age neonate regardless of insulin therapy, or both. Maternal characteristics and diagnostic test results were investigated to identify associations with the high‐risk criteria, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Results: Among 217 patients, 95 (43.8%) were categorized as high risk. After adjusting for confounders, a fasting plasma glucose level at diagnosis of at least 4.66 mmol/L (adjusted OR 2.88, 95% CI 1.51–5.58) and pre‐pregnancy body mass index (calculated as weight in kilograms divided by the square of height in meters) of at least 24 (adjusted OR 3.27, 95% CI 1.60–6.90) were independently associated with meeting the high‐risk criteria. Conclusion: Among Japanese patients with GDM, pre‐pregnancy body mass index and fasting plasma glucose levels could be used to identify high‐risk patients requiring intensive care during pregnancy. Abstract : Japanese patients with gestational diabetes who are obese or have elevated fasting hyperglycemia should be considered at high risk of requiring intensive care during pregnancy.